2019
DOI: 10.3390/su11205793
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes toward Sustainable Development Goals: Evidence from Five Chinese Cities

Abstract: Raising public awareness of the Sustainable Development Goals (SDGs) is a critical prerequisite for their implementation. However, little is known about attitude formation among the public toward SDGs at the national level. We explored this topic in China, a country that has emerged as a leading world economy with strong transformational imperatives to work toward sustainable development. Following Chaiken’s heuristic–systematic model and using data from an online survey with 4128 valid respondents, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 67 publications
5
41
2
2
Order By: Relevance
“…Concerns over sustainability and exposure to SDGs are statistically significant. The latter is consistent with Guan et al [50], who found that knowledge on SDGs is associated with support for SDGs. Trust in organizations was not statistically significant, which was not consistent with international surveys [14,17].…”
Section: Influence Of Sdgs On Japanese Youth Before and During Covid-supporting
confidence: 92%
See 2 more Smart Citations
“…Concerns over sustainability and exposure to SDGs are statistically significant. The latter is consistent with Guan et al [50], who found that knowledge on SDGs is associated with support for SDGs. Trust in organizations was not statistically significant, which was not consistent with international surveys [14,17].…”
Section: Influence Of Sdgs On Japanese Youth Before and During Covid-supporting
confidence: 92%
“…They are sometimes used interchangeably, but not identically, as the former embraces more than the environment. Although their focus was on attitudes toward public support for SDGs, not behavioral changes, Guan et al [50] found that male, younger cohorts, and better educated respondents were more Table 7 lists the logit model used to explore the predictors of behavioral change. The dependent variable was 1 if a respondent made changes and 0 if not; the respondents who answered that they did not know about SDGs (Table 6) were excluded to focus on the impact that SDGs have on behaviors.…”
Section: Influence Of Sdgs On Japanese Youth Before and During Covid-mentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of sustainability development encircle the economic, social and environmental perspectives. As per the findings of previous attitudinal surveys Sonetti, Brown [17]; Guan, Meng [18], the discrepancy between the attitude and action exist. Difference between the thinking and action prevails both at individual and national level.…”
Section: Public Opinion Towards Sustainable Developmentsupporting
confidence: 54%
“…The questionnaire has also been distributed among the selected organizations via internet. The items of the questionnaire has been adopted from the studies of [18,31].…”
Section: Methodsmentioning
confidence: 99%